ESSENCE, CONTENT AND STRUCTURE OF MEDIA COMPETENCE OF THE DOCTOR - Olena Murzina (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article analyzes the psychological and pedagogical literature and interpretations of the definition of «media competence» is made by modern researchers. Information technologies are rapidly developing today and information flow is accelerating, therefore the most important task is to prepare students for life in the modern information environment, to perceive and to understand the information received from the media. This is due to the fact that the growth of media interactivity creates a comfortable space for manipulation, especially for young people who are major media consumers. The process of personal development through the mass media and media technics is media education. The result of media education is the formation of media competence. Media competence is formed as a result of the process of media education and helps a person actively use the possibilities of the information field - television, radio, video, press, the Internet. The result of media education is increasing the level of media competency. Media competence is multidimensional and requires a broad perspective based on a well-developed knowledge structure. The level of media competence can be increased throughout life through the perception and analysis of cognitive, emotional, aesthetic, ethical media information. Media competence enables the formation of an informatively rich educational environment, influences the level of personal media culture, prepares it for safe and effective interaction with modern media space and carries out media educational activities. The level of media education is a significant problem today, and therefore the development of media competence becomes of particular relevance. Media competence includes informational, informatic, communicational and communicative competencies.